Energy-transfer photocatalysis for Minisci C-H (amino)alkylation of heteroarenes using oxime esters as dual-role reagents - Xu, Jun; Zhang, Yuru; Xu, Ruiyuan; Wang, Yuxin; Shen, Jiabin; Li, Wanmei (ORGANIC CHEMISTRY FRONTIERS, 2024)
Utilization of oxime esters as bifunctional reagents in energy-transfer photocatalysis has received considerable attention. However, the reaction type is so far limited to the difunctionalization of alkenes. To confront this limitation and enrich Minisci-type chemistry, herein we have developed a green and practical protocol for Minisci C-H (amino)alkylation of heteroarenes employing diverse oxime esters (from carboxylic acids) as (amino)alkylating reagents. The key to success of this Minisci reaction is that oxime esters play a dual role of (amino)alkylating reagents and oxidants. In addition, the useful approach not only tolerates a wide range of heteroarenes but also features a broad compatibility with different alkyl radicals, including primary-, secondary-, and tertiary-carbon species. Moreover, the practicability of this method is additionally boosted by the functionalization of various amino acids and approved carboxyl-containing drugs. This methodology not only provides a practical strategy for direct decarboxylative C-H (amino)alkylation of heteroarenes, but also broadens the reaction types for the mechanism involving photocatalyzed energy transfer. This study demonstrates a strategy involving photoinduced energy transfer for decarboxylative Minisci C-H (amino)alkylation of heteroarenes employing diverse oxime esters (from carboxylic acids) as (amino)alkylating reagents.